2019
DOI: 10.1186/s12939-019-0946-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of paying national health insurance premium with mobile phone in Ghana: a cross-sectional prospective study

Abstract: IntroductionIn an effort to increase Ghana’s National Health Insurance Scheme (NHIS) enrollment and retention rates, the NHIS introduced membership renewal and premium payment by mobile phone. The success of such an innovation dependents on many factors including personal and community characteristics of members.ObjectiveThe objective of the study is to investigate the determinants of renewing membership and paying the NHIS premium through a mobile phone.MethodologyThe prospective cross-sectional survey was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…58 Some applications to revenue mobilisation and pooling have also been documented: in Ghana, mobile phone apps have simplified payment of health insurance contributions and enrolment reminders. 59 Fourth, little has been documented about any actual adjustments to financing arrangements to facilitate online and digital delivery of PHC, beyond measures to include remote consultations in insurance benefit packages. However, this area is developing rapidly (for example, the introduction of Babyl, an artificial intelligence-supported digital health service provider, i n Rwanda) 60 and often without formal assessment or evaluation.…”
Section: Section 2: the Landscape Of Financing And Organisation Of Phcmentioning
confidence: 99%
“…58 Some applications to revenue mobilisation and pooling have also been documented: in Ghana, mobile phone apps have simplified payment of health insurance contributions and enrolment reminders. 59 Fourth, little has been documented about any actual adjustments to financing arrangements to facilitate online and digital delivery of PHC, beyond measures to include remote consultations in insurance benefit packages. However, this area is developing rapidly (for example, the introduction of Babyl, an artificial intelligence-supported digital health service provider, i n Rwanda) 60 and often without formal assessment or evaluation.…”
Section: Section 2: the Landscape Of Financing And Organisation Of Phcmentioning
confidence: 99%
“…For instance, out of the 40% of the people who have registered for NHIS in Kintampo north municipality as at 2016, only 24.9% have renewed their annual premiums with the remaining (about 75%) citing high cost of premium (GHS30.00; $5.43 per year) as the main barrier (34,35). Distance to and cost of travel to NHIS offices, and delays were also found to be barriers to NHIS registration (34,36).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mobile money users enjoy the benefits of low transaction costs when paying premiums, convenience (do not have to travel to banks to queue and make payments), and reduction in transportation costs. In Ghana, Boaheng et al found that urban and rural informal sector workers were more likely than unemployed to pay their social health insurance premiums using mobile money. The benefits provided by the technology might have reduced the drop‐out rate from NHIF thereby increasing mobile money users' probability of being enrolled in NHIF.…”
Section: Discussionmentioning
confidence: 99%